2013
DOI: 10.1007/s11832-013-0519-2
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis after chest wall resection

Abstract: Background data There has been an increased focus on the role of rib abnormalities in the development of scoliosis. Rib resection may influence the development of scoliosis. Although scoliosis has been identified in patients after thoracotomy, most of the currently available information is from case reports. Methods We examined records of 37 patients who underwent a chest wall or rib resection for rib lesions at our institution during the period of 1992 to 2005. Adequate data was available in 21 patients. We g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 31 publications
1
37
1
Order By: Relevance
“…Although changes in Cobb angle after treatment of scoliosis have been studied extensively (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), their relationships to tidal volumes to our knowledge have not been examined. In this study, we found only one significant association for Cobb angle, namely lumbar Cobb angle measurement with LHTV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although changes in Cobb angle after treatment of scoliosis have been studied extensively (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), their relationships to tidal volumes to our knowledge have not been examined. In this study, we found only one significant association for Cobb angle, namely lumbar Cobb angle measurement with LHTV.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the prime quantitative measures for corrective procedures have remained the anteroposterior and lateral radiographic Cobb angles (6)(7)(8)(9)(10), although these are essentially measurements of only the scoliotic disease. There is no useful correlation between Cobb angles and lung vital capacity before or after operation (11), which limits their health assessment value (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Scoliosis may develop shortly after treatment or many years later, such as during their adolescent growth spurt. 19 Children after cardiothoracic surgery experience a higher risk of developing a spinal curve compared with their otherwise healthy peers, 20 and individuals who have had disruption at or above the level of the fifth rib are at greatest risk. 19 Idiopathic scoliosis has an unknown etiology, likely because of a combination of hereditary, hormonal, and environmental factors, and an unclear inheritance pattern.…”
Section: Etiologymentioning
confidence: 99%
“…19 Children after cardiothoracic surgery experience a higher risk of developing a spinal curve compared with their otherwise healthy peers, 20 and individuals who have had disruption at or above the level of the fifth rib are at greatest risk. 19 Idiopathic scoliosis has an unknown etiology, likely because of a combination of hereditary, hormonal, and environmental factors, and an unclear inheritance pattern. 21 Because mild scoliosis was likely not detected in past generations, an absent family history should not exclude the diagnosis.…”
Section: Etiologymentioning
confidence: 99%